The fully compressed subgroup membership problem - Linton, M (Elsevier, 2023)
Suppose that F is a free group and k is a natural number. We show that the fully compressed membership problem for k-generated subgroups of F is solvable in polynomial time. In order to do this, we adapt the theory of Stallings' foldings to handle edges with compressed labels. This partially answers a question of Markus Lohrey.